2017
DOI: 10.1007/s00360-017-1082-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal adaptations in energy budgeting in the primate Lepilemur leucopus

Abstract: The spiny forest of South Madagascar is one of the driest and most unpredictable habitats in Africa. The small-bodied, nocturnal primate Lepilemur leucopus lives in this harsh habitat with high diurnal and seasonal changes in ambient temperature. In this study, we investigated seasonal adaptions in energy budgeting of L. leucopus, which allow it to live under these conditions by measuring resting metabolic rate using open-flow respirometry. No signs of heterothermy were detected, and resting metabolic rate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Our prediction on seasonality was supported; we found that temperature positively affected the activity of Japanese macaques during the studied year, indicating that macaques were more active when the thermal conditions were favorable. The thermoneutral zone, i.e., the ambient temperature range that does not require animals to allocate additional energetic costs to thermoregulation, is reported to be 5–28°C for colobus monkeys [ 49 ], 20–27°C for titis [ 50 ], 25–30 for tarsiers [ 51 ], 25–32°C for sportive lemurs [ 52 ], above 27°C for mouse lemurs [ 53 ], 27–34°C for pygmy marmosets [ 54 ] and 17–28°C for chimpanzees [ 55 ]. Even though the thermoneutral zone for macaques has not been reported, a feeding experiment on captive macaques indicated that they changed food intake and food selection when room temperature decreased from 29 to 15°C [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our prediction on seasonality was supported; we found that temperature positively affected the activity of Japanese macaques during the studied year, indicating that macaques were more active when the thermal conditions were favorable. The thermoneutral zone, i.e., the ambient temperature range that does not require animals to allocate additional energetic costs to thermoregulation, is reported to be 5–28°C for colobus monkeys [ 49 ], 20–27°C for titis [ 50 ], 25–30 for tarsiers [ 51 ], 25–32°C for sportive lemurs [ 52 ], above 27°C for mouse lemurs [ 53 ], 27–34°C for pygmy marmosets [ 54 ] and 17–28°C for chimpanzees [ 55 ]. Even though the thermoneutral zone for macaques has not been reported, a feeding experiment on captive macaques indicated that they changed food intake and food selection when room temperature decreased from 29 to 15°C [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Values for SMR and mass were log-transformed, because metabolism is a power function of mass(Orlofske and Hopkins 2009;Orlofske et al 2017). Only the lowest 30% of the values were used to ensure that only data of resting individuals were included in analyses, thereby omitting any phases of stress, disturbance, or activity(Orlofske and Hopkins 2009;Peck and Moyano 2016;Orlofske et al 2017;Bethge et al 2017).…”
mentioning
confidence: 99%
“…It is unclear why, however, L. fleuretae did not show a timeminimising strategy as other Lepilemur spp. (e.g., L. leucopus [Bethge et al, 2017]; L. sahamalaza [Mandl et al, 2018]). This genus has received relatively little attention in moist forests, so we cannot exclude that the pattern we observed is not uncommon in this habitat.…”
Section: Discussionmentioning
confidence: 99%